Do karate fighters use situational probability information to improve decision-making performance during on-mat tasks?. Issue 16 (17th August 2016) - Milazzo, Nicolas; Farrow, Damian; Ruffault, Alexis; Fournier, Jean F.
ABSTRACT: This study examined the contribution of situational probability information to the perceptual and cognitive processes underlying decision-making behaviour during in situ Karate performance. Experts and novices were required to make decisions about various attacks in different fight scenarios. The order in which the fight situations were presented was modified in order to provide advanced probability information and identify whether fighters were able to use the latter information to make better decisions. Specifically, one of the attacks was repeated every four actions. Results revealed that experts were more accurate and faster than their less skilled counterparts to block and counterattack the opponent. The experts picked up the occurrence of the attack pattern after the fifth repetition whereas novices did not. This enabled experts to improve decision time and decision accuracy. Findings suggest that such superiority could stem from the perceptual and cognitive skills possessed by the experts, thus giving them the opportunity to recognise a situation more easily. This was reinforced by gaze behaviour which demonstrated that experts used a more efficient search strategy involving fewer fixations of longer duration on a lesser number of areas relative to the novices. Moreover, experts generated more refined karate-specific knowledge structures compared with the novices.